Development of a μO-Conotoxin Analogue with Improved Lipid Membrane Interactions and Potency for the Analgesic Sodium Channel Na(V)1.8 - Deuis, Jennifer R. (J Biol Chem, 2016)
The μO-conotoxins MrVIA, MrVIB, and MfVIA inhibit the voltage-gated sodium channel Na(V)1.8, a well described target for the treatment of pain; however, little is known about the residues or structural elements that define this activity. In this study, we determined the three-dimensional structure of MfVIA, examined its membrane binding properties, performed alanine-scanning mutagenesis, and identified residues important for its activity at human Na(V)1.8. A second round of mutations resulted in (E5K,E8K)MfVIA, a double mutant with greater positive surface charge and greater affinity for lipid membranes compared with MfVIA. This analogue had increased potency at Na(V)1.8 and was analgesic in the mouse formalin assay.